Joki Skripsi: Jalan Pintas Pemuda Indonesia Menghadapi Ketidakpastian Dunia Kerja - Fahmi, Ridwan Tajul; Rofiqiyah, Hifni Azizatur (Jurnal Studi Pemuda, 2023)
This study examines youths who make “joki skripsi” and “joki tugas” as side jobs. The difficulty of finding the right job for college graduates makes youth trapped in the precarious work. This happens because of the gap between the output and the types of work available. Young people need jobs that are right for them and able to afford what they don't get at their primary jobs. We conducted in-depth interviews with three young “joki tugas” in East Java to discover their reflective steps towards precarious work. We found that in youth making “joki tugas” as a reflective effort to mitigate two risks. The first risk is financial insecurity when they are unemployed. The second risk is the threat of deskilling because their work does not require high skills. This study seeks to enrich the study of “joki skripsi” in Indonesia, their relation to the initiation of the world of work, and the demands for youth to be reflective in dealing with these conditions.